2010
DOI: 10.1073/pnas.1011564107
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between internal forces, body stiffness, and fluid environment in a neuromechanical model of lamprey swimming

Abstract: Animal movements result from a complex balance of many different forces. Muscles produce force to move the body; the body has inertial, elastic, and damping properties that may aid or oppose the muscle force; and the environment produces reaction forces back on the body. The actual motion is an emergent property of these interactions. To examine the roles of body stiffness, muscle activation, and fluid environment for swimming animals, a computational model of a lamprey was developed. The model uses an immerse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
291
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(306 citation statements)
references
References 37 publications
13
291
1
1
Order By: Relevance
“…As discussed earlier, the choice of performance measure for optimization is not unique. For comparison, we provide results for the minimization of power coefficients, namely of power output-based C M P ; P L mech =P 0 (used in Tytell et al [14]) and of power consumption-based C T P ; P L musc =P 0 (suggested in Yates [39]). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed earlier, the choice of performance measure for optimization is not unique. For comparison, we provide results for the minimization of power coefficients, namely of power output-based C M P ; P L mech =P 0 (used in Tytell et al [14]) and of power consumption-based C T P ; P L musc =P 0 (suggested in Yates [39]). …”
Section: Resultsmentioning
confidence: 99%
“…The model also neglects vortex shedding, lateral flow separation and viscous drag (relevant at lower Re numbers [13]). Despite these restrictions, Lighthill's model has been shown to provide sufficiently accurate values for the obtained lateral force [14,43]. It is important to point out, however, that our primary interest is in the correct scaling of quantities with Re and the proper dependence on kinematic and geometric parameters, rather than in the quantitative accuracy (requiring substantially greater computational cost).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high complexity, mathematical modeling is essential for understanding mechanisms underlying neuronal information processing in the CNS. Taking animal locomotion as a tractable focus of study, a number of models have previously been developed, ranging from neuronal circuit models for CPGs (44)(45)(46)(47) and body-fluid interactions during swimming (35,48) to integrated neuromechanical models for locomotion (49)(50)(51). An ultimate goal is to have dynamical models that are simple and amenable not only to numerical simulations but also to analytical studies, and which are fully validated by experimental data, with demonstrated predictability under perturbed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sensors at the nose region directly in front of the eye can sense dorsalventral flows, such as those generated by vertical movements of the fish or shed vortices [4]. Bioinspired underwater robotics is one field of research that can address robotic navigational challenges and provide us insights into how animals achieve successful aquatic navigation [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%